Analisis Kinerja Keuangan Bank BUMN di Bursa Efek Indonesia Periode 2019-2023 - Lailatus Sa’adah; Rihlatil Hajjah; Andri Tiansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the financial performance of state-owned banks (BUMN) listed on the Indonesia Stock Exchange during the period of 2019–2023 based on profitability ratios (ROA, ROE) and operational efficiency (CIR). The results show that Bank Mandiri and BRI had the best performance, with significant improvements in efficiency and profitability, achieving ROA of 2.76% and 3.08% and ROE of 20.89% and 19.09% in 2023. Meanwhile, Bank BNI experienced fluctuations in its profitability ratios, with ROA increasing to 2.25% in 2023, although slightly lower than the previous year. Nevertheless, Bank BNI showed relatively stable operational efficiency, with CIR ranging between 50% and 60%. Bank BTN, while having the lowest performance, showed significant improvement throughout the study period. This study provides important insights for investors and policymakers in understanding the dynamics of the national banking sector.